Plasma ACE activity after aerobic exercise training is related to sleep in migraine patients: A secondary, per protocol analysis - Oliveira, Arão Belitardo; Visniauskas, Bruna; Chagas, Jair Ribeiro; Peres, Mario Fernando Prieto (Headache Medicine, 2020)
Angiotensin converting enzyme-1 (ACE) has been implicated in sleep regulation and nociception. In a secondary, per-protocol analysis, we investigated the effect of a 12-week aerobic exercise program on plasma ACE activity (primary outcome variable), migraine clinical outcomes, and psychometric scores between migraine and control, non-headache participants. Fifty-nine participants (migraine: n=31 and control: n=28) gave signed consent form and were per-protocol analyzed. At baseline, there were no differences between groups for ACE activity. After the intervention period, the ACE activity increased in the migraine exercise group compared to control waitlist group [mean difference (95% CI) = 33.8 nM.min– 1.mg–1 (1.0, 66.5), p = 0.02]. Among patients, the migraine exercise group showed greater numeric reduction in the number of sleep deprivation-triggered attacks compared to migraine waitlist group (-21 vs -8, respectively), and lower insomnia scores [mean difference (95% CI) = -0.625 (-996, -254), p = 0.001]. There was an inverse correlation between BECK-II insomnia domain scores and ACE activity (r = -0.53, p = 0.035). This study suggests that aerobic exercise training increases plasma ACE activity with possible implication on sleep regulation in migraine patients.